Acute Exposure to Fluoxetine Alters Aggressive Behavior of Zebrafish and Expression of Genes Involved in Serotonergic System Regulation - Theodoridi, Antonia; Tsalafouta, Aleka; Pavlidis, Michail (Frontiers in Neuroscience, 2017)
Zebrafish, Danio rerio, is an emerging model organism in stress and neurobehavioral studies. In nature, the species forms shoals, yet when kept in pairs it exhibits an agonistic and anxiety-like behavior that leads to the establishment of dominant-subordinate relationships. Fluoxetine, a selective serotonin reuptake inhibitor, is used as an anxiolytic tool to alter aggressive behavior in several vertebrates and as an antidepressant drug in humans. Pairs of male zebrafish were held overnight to develop dominant – subordinate behavior, either treated or non-treated for 2 h with fluoxetine (5 mg L-1), and allowed to interact once more for 1 h. Behavior was recorded both prior and after fluoxetine administration. At the end of the experiment, trunk and brain samples were also taken for cortisol determination and mRNA expression studies, respectively. Fluoxetine treatment significantly affected zebrafish behavior and the expression levels of several genes, by decreasing offensive aggression in dominants and by eliminating freezing in the subordinates. There was no statistically significant difference in whole-trunk cortisol concentrations between dominant and subordinate fish, while fluoxetine treatment resulted in higher (P = 0.004) cortisol concentrations in both groups. There were statistically significant differences between dominant and subordinate fish in brain mRNA expression levels of genes involved in stress axis (gr, mr), neural activity (bdnf, c-fos) and the serotonergic system (htr2b, slc6a4b). The significant decrease in the offensive and defensive aggression following fluoxetine treatment was concomitant with a reversed pattern in c-fos expression levels. Overall, an acute administration of a selective serotonin reuptake inhibitor alters aggressive behavior in male zebrafish in association with changes in the neuroendocrine mediators of coping styles.